Carolina Christmas : Archibald Rutledge's Enduring Holiday Stories - Rutledge, Archibald, 1883-1973 (Book collections on Project MUSE., 2010)
A collection of holiday tales, poems, and recipes celebrating hearth and hunt in the South of yesteryear.